Medical safety in boxing: Administrative, ethical, legislative, and legal considerations - Schwartz, M. B. (Clinics in Sports Medicine, 2009)
The roles and responsibilities of the ringside physician are complex and have evolved into a unique specialty in sport medicine. In addition to the medical aspects of ringside medicine, the doctor is now responsible for many administrative, ethical, and legal considerations. This article reviews and details the numerous roles the ringside physician plays in the sport of boxing.